PENGARUH ORIENTASI KEWIRAUSAHAAN, ORIENTASI PASAR DAN KEUNGGULAN BERSAING TERHADAP KINERJA INDUSTRI KECIL DAN MENENGAH (Studi pada IKM Furniture di Kota Semarang) - Astri Wulaningtyas; widiartanto widiartanto (Universitas Diponegoro, 2018)
The performance of a business unit can be affected by a variety of factors, both internal and external company factors. The purpose of this research is to know the influence of the entrepreneurial orientation, market orientation and competitive advantage against the business performance of small and medium enterprises. The research type is explanatory research. This study uses purposive sampling techniques against small and medium furniture industries in Semarang. Data collecting using a questionnaire and interviews. Data analysis using simple and doubled linier regression analysis with IBM SPSS 20. Results of statistical analysis known that together the entrepreneurial orientation, market orientation, and competitive advantage effect on the business performance.The conclusion from this study is that there is a positive and significant influence between entrepreneurial orientation, market orientation, and competitive advantage to business performance of the small and medium furniture industries in Semarang. Research suggest that IKM improve proactivity and looking for opportunities in entrepreneurship, improve market orientation and competitiveness so that IKM can continue to survive in the midst of the current competition.